IGARSS 2018 - 2018 IEEE International Geoscience and Remote Sensing Symposium 2018
DOI: 10.1109/igarss.2018.8518720
|View full text |Cite
|
Sign up to set email alerts
|

The Indian-French Trishna Mission: Earth Observation in the Thermal Infrared with High Spatio-Temporal Resolution

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 17 publications
0
46
0
1
Order By: Relevance
“…For example, in July at 10:00, 29 observations were identified clear-sky at Tonzi Ranch, CA on average, but only 16 at Chestnut Ridge, TN. In comparison to the global statistics for cloud-free MODIS observations produced by Lagouarde et al [23] with a 5 km resolution, we found that ground-based estimates were usually slightly higher than MODIS-derived products. This may be due to differences in spatial scales, i.e., a partly cloudy sky can significantly affect a km-scale satellite pixel and be flagged by the cloud mask algorithm without affecting in situ observations.…”
Section: Scaling Et From Instantaneous Observations To Daytime Averagesmentioning
confidence: 49%
See 2 more Smart Citations
“…For example, in July at 10:00, 29 observations were identified clear-sky at Tonzi Ranch, CA on average, but only 16 at Chestnut Ridge, TN. In comparison to the global statistics for cloud-free MODIS observations produced by Lagouarde et al [23] with a 5 km resolution, we found that ground-based estimates were usually slightly higher than MODIS-derived products. This may be due to differences in spatial scales, i.e., a partly cloudy sky can significantly affect a km-scale satellite pixel and be flagged by the cloud mask algorithm without affecting in situ observations.…”
Section: Scaling Et From Instantaneous Observations To Daytime Averagesmentioning
confidence: 49%
“…Two overpass times have been considered to represent the nominal times of a morning and afternoon satellite overpass: 10:00 and 13:00 The 10:00 overpass corresponds to instruments like the Thermal Infrared Sensor (TIRS) onboard Landsat-8, the Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER), MODIS onboard Terra or the Sea and Land Surface Temperature Radiometer (SLSTR) onboard Sentinel 3, and the afternoon overpass to instruments like MODIS onboard Aqua or VIIRS onboard the Suomi National Polar-Orbiting Partnership (Suomi-NPP) and Joint Polar Satellite System (JPSS) spacecrafts, for example. The afternoon overpass is also the preferred overpass time for missions in preparation, such as TRISHNA or LSTM [22,23]. The impact of acquisition time on the ability to detect water stress and then derive daily ET estimates in accordance with the actual stress level and the stability of temperature measurements was discussed by [54,55].…”
Section: Generation Of Series Of Observations With Different Revisit mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the existing two-source models (SPARSE [33], ESVEP [41], ALEXI [43], TSEB [32]), the thermal-based two-source energy balance (TSEB) [32] was chosen for its simplicity and because it has been shown to accurately predict LE in different contexts, including sparse canopy in semi-arid areas [9,21,25,34,38]. Until the launch of a future high-resolution and high-repetitiveness mission in the thermal infrared domain [44], the possibilities in terms of LST products are limited to the Moderate Sensors Resolution Imaging Spectroradiometer (MODIS) (1 km and a daily revisit time) and Landsat (60 to 100 m resolution, 16 days). The question arises as to what is the required level of heterogeneity representation in terms of input surface variables to get accurate predictions of convective fluxes (H and LE) with the TSEB model based on the available remote sensing products?…”
Section: Introductionmentioning
confidence: 99%
“…Several projects are currently under study to develop thermal satellites with high enough spatial resolution and revisit capacities to characterize the microscale structure of SUHIs. These are the Indian (ISRO)-French (CNES) mission TRISHNA [13], the European (ESA) LSTM [14], and HyspIRI in NASA/JPL [15]. But such missions lack in their spatial resolution of about 50-60 m and are not able to discern the local LST on an urban object scale.…”
Section: Introductionmentioning
confidence: 99%